2021
DOI: 10.36076/ppj.2021.24.153-163
|View full text |Cite
|
Sign up to set email alerts
|

Receptor and Molecular Targets for the Development of Novel Opioid and Non-Opioid Analgesic Therapies

Abstract: BACKGROUND: Although conventional pain relief therapeutics have centered around μ-opioid agonists, these drugs are limited by adverse side effects, including respiratory depression and addiction potential. The ongoing opioid epidemic has galvanized research into novel analgesic therapies with more favorable profiles. New pharmacologic agents have been developed to target neuronal pathways involved in pain sensation. Certain receptors have been recognized to mediate nociceptive transmission, central sensitizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…TRPV1 channels are expressed predominantly in the afferent sensory neurons and are particularly abundant in C and Aδ nociceptive fibers, where they play a key role in the detection of noxious painful stimuli [ 18 ]. For many years TRPV1 has been recognized as one of the most promising and widely explored molecular targets for new and effective analgesics [ 19 , 20 ]. The results of hitherto studies (including clinical trials) have shown that TRPV1 antagonists may be useful in the treatment of pain of various origins, e.g., inflammatory, neuropathic, postoperative, visceral, cancer, and migraine pain [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…TRPV1 channels are expressed predominantly in the afferent sensory neurons and are particularly abundant in C and Aδ nociceptive fibers, where they play a key role in the detection of noxious painful stimuli [ 18 ]. For many years TRPV1 has been recognized as one of the most promising and widely explored molecular targets for new and effective analgesics [ 19 , 20 ]. The results of hitherto studies (including clinical trials) have shown that TRPV1 antagonists may be useful in the treatment of pain of various origins, e.g., inflammatory, neuropathic, postoperative, visceral, cancer, and migraine pain [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest iFentanylSnFR2.0’s optical response can be calibrated to the biofluid, meeting existing form factors for both rapid point-of-care tests and continuous monitors comparable to a fluorescence-based continuous glucose monitor 69 . This result is particularly useful for addressing the proliferation of synthetic fentanyl analogs 70,71 and research compounds such as unconventional µ -opioids and synthetic kappa opioids under consideration in therapeutic applications 72,73 . Using iLevorphanolSnFR alongside methadone maintenance therapy would require controlling for S-methadone using another biosensor.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new treatment strategies and optimization of existing ones, particularly non-opioid based, have been central to pain research. This includes developing new analgesic drugs, optimizing existing ones, and exploring alternative pain management strategies, including physical therapy, cognitive-behavioral therapy, and mindfulness [ 28 ]. Recently, researchers have attempted to tailor pain management strategies to individual patient characteristics and needs.…”
Section: Discussionmentioning
confidence: 99%